Ensino de leitura e combate ao preconceito contra a mulher negra: proposta de atividade com a HQ Os Santos – uma tira de humor ódio - Freire, Georgia Carla Barreto (2024)
The present work of propositional and qualitative nature contributes to teaching reading and to the expansion of language skills through the reading of the comic book genre as support for the discussion and the fight against prejudice towards black women through Portuguese Language classes in the 9th year of Elementary School. Furthermore, this research describes to what extent the expansion of these skills directs students' learning in order to make the process more meaningful by completing the steps of the reading class presented by Leurquin (2014). For that, it was presented, by the end of this study, an activity notebook divided into six modules that would guide the work with the categories of the theoretical framework of Sociodiscursive Interactionism - ISD (BRONCKART, 1999), focusing on production context (capacity for action), voices and modalizations (linguistic-discursive skills), using the comic book Os Santos – a story of humor hate in order to demonstrate how prejudice against black women is marked in society. Moreover, contributions from the studies of Grammar of Visual Design– GVD (KRESS and VAN LEUWEEN, 1996) made it possible the comprehension of multisemiotic aspects of the text. The theoretical support of this work is also based on authors such as Kleiman (2016), Smith (1989) and Braggio (1992), concerning the work with reading, models, conceptions and planning; Dolz and Schneuwly (2004), regarding the expansion of language skills, in addition to others who helped in the development of this research. Through this work, in line with the proposal in which it is inserted, it is expected that basic education teachers will have another instrument for reading classes, with focus on interactive classes, which value all stages from planning to results, since reading needs to bring meaning and critical thinking, so the subject becomes an agent of change according to their reality.